2012
DOI: 10.1093/hmg/dds510
|View full text |Cite
|
Sign up to set email alerts
|

Developmental abnormalities in mouse embryos lacking the HDL receptor SR-BI

Abstract: The srbi gene encodes a lipoprotein receptor with high affinity for high density lipoprotein that is mainly expressed in the liver and in steroidogenic tissues. Disruption of this gene in mice and mutations in humans lead to alterations in lipoprotein metabolism and/or fertility. During murine development, scavenger receptor class B member I (SR-BI) is present in the yolk sac and the placenta and is only expressed in the embryo itself late in gestation. In humans, it has been detected in trophoblast cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 50 publications
2
23
0
Order By: Relevance
“…TGC play a critical role in embryonic uptake of various nutrients from the maternal blood supply before the establishment of a mature placenta 6 . Despite the prominent role of SR-BI in cholesterol uptake 1 and the key role of cholesterol during embryonic development 7 , we have shown that the embryonic cholesterol content is similar in SR-BI +/+ and SR-BI −/− embryos 5 .…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…TGC play a critical role in embryonic uptake of various nutrients from the maternal blood supply before the establishment of a mature placenta 6 . Despite the prominent role of SR-BI in cholesterol uptake 1 and the key role of cholesterol during embryonic development 7 , we have shown that the embryonic cholesterol content is similar in SR-BI +/+ and SR-BI −/− embryos 5 .…”
Section: Introductionmentioning
confidence: 61%
“…This evidence, together with the fact that SR-BI is present in murine trophoblasts involved in maternal-foetal nutrient exchange at different stages of gestation 4 , led researchers to postulate that this HDL receptor might be involved in embryonic development. We recently showed that nearly 50% of SR-BI −/− embryos fail to close the anterior neural tube and develop cranial NTD and exencephaly 5 , leading to perinatal death, which explains the deviation from the Mendelian ratio previously reported in weaned SR-BI null mice 3 . Among the spectrum of defective neurulation conditions conferred by abnormal closure at different portions of the neural tube, only cranial NTD is observed in SR-BI −/− embryos.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Absence of these cholesterol transporters in mouse models show different phenotypes, ranging from early developmental arrest and exencephaly in scavenger receptor class B deficient embryos 16 , to no birth defects in low density lipoprotein receptor knockout pups 17 .…”
Section: Accepted Articlementioning
confidence: 99%
“…All rights reserved. closure and fetal growth (Santander et al, 2013). Previous research had demonstrated that SR-B1 was expressed in theca internal cells (T-I) at all stages of follicular development and in corpus luteum cells (CL) of rat ovaries (Johnson et al, 1998;Mizutani et al, 1997).…”
Section: Introductionmentioning
confidence: 99%